Strategi Pengiklanan Dan Pelayanan Pariwisata Di Indonesia Pasca Pandemi Covid-19 - Rizki Nugraha; Vickrham Achmad (Peneliti.net, 2023)
The COVID-19 pandemic has changed various aspects of life including economic sectors such as tourism. During the Covid-19 pandemic, Indonesia's tourism sector experienced a drastic decline. At the same time, an innovation strategy is needed so that tourism can survive amid the Covid-19 pandemic. This study aims to introduce strategies to increase tourism in Indonesia through improvement and service strategies. This study uses the literature review method or literature study where reading then compares and analyzes previous research as a reference for writing this paper. The results of this study are improving services that can be carried out, one of which is by ensuring that the place is sterile and kept clean considering that we are currently still in the transition period of Covid-19. In addition, there are defense strategies that can be used by tourism managers such as advertising, social media and endorsements